Implementasi Pursed Lip Breathing Untuk Mengurangi Sesak Napas Pada Pasien Ppok Di Rs Harapan Dan Doa Bengkulu - Agisyha, Resta; Ramlis, Ravika; Aprianti, Delta (Utami Publisher, 2025)
According to data from the World Health Organization (WHO), Chronic Obstructive Pulmonary Disease (COPD) ranks as the third leading cause of death worldwide, with a death toll reaching 3.23 million lives in 2024. In Indonesia, the prevalence of COPD continues to rise each year. Based on medical record data from Harapan dan Doa Hospital in Bengkulu City, COPD cases increased from 37 cases in 2022 to 46 cases in 2024. The purpose of this study is to examine the implementation of pursed lip breathing exercises in reducing shortness of breath in COPD patients at Harapan dan Doa Hospital, Bengkulu City, in 2025. This research uses a descriptive method by presenting facts according to the data obtained. The results show that after performing pursed lip breathing exercises for three consecutive days, twice in the morning and evening for 15 minutes, there was a decrease in the level of shortness of breath in Mr. H according to the Borg scale, from a score of 4 (moderate shortness of breath) to a score of 2 (mild shortness of breath). This technique has proven effective in helping patients manage their breathing and enhance comfort while breathing. The implementation of pursed lip breathing exercises has a significant impact on reducing shortness of breath in COPD patients. This study is expected to enhance knowledge for students, readers, and healthcare professionals regarding the pursed lip breathing technique as a non-pharmacological intervention to address shortness of breath.